High on habits - Hilário, Monica R.; Costa, Rui M. (Frontiers in Neuroscience, 2008)
The neural circuits involved in learning and executing goal-directed actions, which are governed by action-outcome contingencies and sensitive to changes in the expected value of the outcome, have been shown to be different from those mediating habits, which are less dependent on action-outcome relations and changes in outcome value. Extended training, different reinforcement schedules, and substances of abuse have been shown to induce a shift from goal-directed performance to habitual performance. This shift can be beneficial in everyday life, but can also lead to loss of voluntary control and compulsive behavior, namely during drug seeking in addiction. Although the brain circuits underlying habit formation are becoming clearer, the molecular mechanisms underlying habit formation are still not understood. Here, we review a recent study where Hilario et al. established behavioral procedures to investigate habit formation in mice in order to investigate the molecular mechanisms underlying habit formation. Using those procedures, and a combination of genetic and pharmacological tools, the authors showed that endocannabinoid signaling is critical for habit formation.